Coating process of amorphous nanocrystalline magnetic powder and preparation method of magnetic powder core

The coating in the amorphous magnetic powder core is solved by plasma chemical vapor deposition technology, and the problems of long coating time and high temperature in the prior art are solved, efficient and uniform SiO2 film coating is achieved, and the performance of the magnetic powder core is improved.

CN119650285APending Publication Date: 2025-03-18TIZ ADVANCED ALLOY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411818379.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively realize high permeability and low loss insulating coating in amorphous magnetic powder core, and the commonly used coating processes have problems such as long time and high temperature, which affects production efficiency and performance.

Method used

Plasma chemical vapor deposition method is used to coat the amorphous magnetic powder below the crystallization temperature. The SiO2 film is uniformly deposited on the surface of the magnetic powder through rotary chemical vapor deposition technology to achieve efficient insulation coating.

Benefits of technology

It realizes efficiently coating the surface of the magnetic powder with uniform and dense oxide film in a short time, improves the anti-rust performance and insulation characteristics of the magnetic powder core, and maintains the characteristics of high magnetic permeability and low loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650285A_ABST
    Figure CN119650285A_ABST
Patent Text Reader

Abstract

The invention provides a coating process of amorphous nanocrystalline magnetic powder and a preparation method of a magnetic powder core. The coating process comprises the following steps: mixing magnetic powder, a coupling agent and an ethanol solution; the coupled magnetic powder is placed in a glass deposition tube and vacuumized; introducing a mixed gas of Ar and N2O into the glass deposition tube; heating the glass deposition tube to a first preset temperature, and starting the rotation of the glass deposition tube; starting a microwave generator to generate plasma, performing plasma pretreatment on the magnetic powder, and vacuumizing again; mixed gas of Ar, N2O and SiH4 is introduced into the glass deposition tube, a microwave generator is started to generate plasma, and after the mixed gas reacts, a SiO2 film is deposited on the surface of the magnetic powder; and discharging the reaction gas in the glass deposition tube, cooling the magnetic powder along with the furnace, and taking out the magnetic powder. According to the method, a uniform and compact oxide film can be efficiently deposited on the surface of the magnetic powder within a short time below the crystallization temperature of the amorphous magnetic powder, and the characteristics of high rust resistance and high magnetic conductivity are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the technical field of magnetic functional materials, and in particular to a coating process for amorphous nanocrystalline magnetic powder and a preparation method for a magnetic powder core. [Background technology]

[0002] Soft magnetic powder core is a composite material formed by insulating and coating soft magnetic powders in sequence. Soft magnetic powder cores are divided into iron powder cores, iron silicon powder cores, iron silicon aluminum powder cores, iron nickel powder cores, iron nickel molybdenum powder cores, amorphous powder cores, nanocrystalline powder cores, etc. according to the type of magnetic powder. Among them, amorphous / nanocrystalline soft magnetic alloys are ideal alloy materials for preparing magnetic powder cores because of their high magnetic permeability and high resistance.

[0003] In the preparation process of magnetic powder cores, adding insulating materials between magnetic powder particles can not only block the eddy current path, increase resistivity and reduce powder core loss, but also protect the magnetic powder and block direct contact between the magnetic powder and the air. However, adding too much insulating material, including insulating agents and binders, to the magnetic powder core will seriously affect the magnetic permeability. According to simulations, when the total volume fraction of insulating material added to the powder core reaches 2%, the magnetic permeability will drop by half, and when the total volume fraction of the added insulating material reaches 10%, the magnetic permeability will drop by 80%. Therefore, how to obtain high insulation while maintaining high magnetic permeability of the magnetic core is a difficulty in the current insulation coating process.

[0004] The Chinese invention patent application with publication number CN116435085A discloses a method of in-situ generation of oxide thin film on the surface of amorphous magnetic powder by sol-gel method. Although a dense coating layer can be generated, the sol-gel process takes a long time, usually requiring a reaction time of ten hours, and the solution concentration needs to be strictly controlled during the process, which is not suitable for large-scale production. The Chinese invention patent with publication number CN112466589B discloses a coating process of depositing oxide thin film on the surface of magnetic powder by chemical vapor deposition. The prepared thin film can indeed be evenly wrapped around the outside of the magnetic powder; however, the temperature required for atmospheric pressure vapor deposition of oxide thin film is relatively high (usually above 700°C). When the temperature is higher than the crystallization temperature, the amorphous alloy is prone to direct crystallization and deterioration of performance, so it is not suitable for use in amorphous / nanocrystalline magnetic powder.

[0005] In summary, the coating process needs to be further improved and an insulating coating method suitable for amorphous powders needs to be developed to obtain soft magnetic powder cores with high magnetic permeability and low loss. [Summary of the invention]

[0006] The technical problem to be solved by the present invention is to provide a coating process for amorphous nanocrystalline magnetic powder and a method for preparing a magnetic powder core. By utilizing plasma chemical vapor deposition, the coating can be performed below the crystallization temperature of the amorphous magnetic powder, thereby achieving a short time and efficient deposition of a uniform and dense oxide film on the surface of the magnetic powder, achieving the characteristics of high rust resistance, high magnetic permeability and low loss.

[0007] The present invention is achieved in that:

[0008] In a first aspect, a coating process for amorphous nanocrystalline magnetic powder is provided, the coating process comprising the following steps:

[0009] Step 1, mixing magnetic powder and coupling agent with ethanol solution for coupling, and drying after mechanical stirring;

[0010] Step 2, placing the coupled magnetic powder in a glass deposition tube for vapor deposition, and evacuating the glass deposition tube;

[0011] Step 3, introducing a mixed gas of Ar and N2O into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure;

[0012] Step 4: using a heating device to heat the glass deposition tube to a first preset temperature, and starting the glass deposition tube to rotate at a preset speed, thereby driving the magnetic powder in the glass deposition tube to move;

[0013] Step 5, turning on the microwave generator to generate plasma and performing plasma pretreatment on the magnetic powder; after the discharge reaches a preset discharge time, turning off the microwave generator and evacuating the glass deposition tube again;

[0014] Step 6, introducing a mixed gas of Ar, N2O and SiH4 into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure, and keeping the glass deposition tube in a sealed state;

[0015] Step 7, turning on the microwave generator again to generate plasma, so that the mixed gas reacts and deposits a SiO2 film on the surface of the magnetic powder;

[0016] Step 8. After reaching the preset deposition time, turn off the heating equipment; introduce pure Ar gas into the glass deposition tube to discharge the reaction gas in the glass deposition tube, and after discharge, turn off the gas source and stop the rotation of the glass deposition tube; take out the magnetic powder after cooling it in the furnace to obtain the insulating coated magnetic powder.

[0017] Furthermore, in step 1, the magnetic powder is iron-based amorphous magnetic powder, and the composition of the iron-based amorphous magnetic powder is any one of FeSiB, FeSiBP, FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, and FeSibBPCNbCu, or a mixture of multiple thereof;

[0018] The coupling agent is a silane coupling agent, and the silane coupling agent is one or a mixture of KH550, KH560, KH570, and KH792, and the amount of the coupling agent is 0.3-1wt% of the weight of the magnetic powder;

[0019] The drying after mechanical stirring specifically includes: drying after mechanical stirring for 30 minutes.

[0020] Furthermore, in step 2 and step 5, the vacuuming of the glass deposition tube is specifically: the vacuum degree of the glass deposition tube is drawn to less than 1×10 -2 Pa.

[0021] Furthermore, in step 3 and step 6, the preset pressure is 50-300 Pa; and in step 6, the gas flow ratio of N2O and SiH4 is 2:1-4:1.

[0022] Furthermore, in step 4, the first preset temperature is 100-300° C., and the preset speed is 10-30 r / min.

[0023] Furthermore, in step 5 and step 7, the power of the microwave generator is 10-100 W; and in step 5, the preset discharge time is 1-10 minutes.

[0024] Furthermore, in step 8, the preset deposition time is 1-10 minutes.

[0025] In a first aspect, a method for preparing a magnetic powder core is provided, wherein the method requires the use of an insulating coated magnetic powder, wherein the insulating coated magnetic powder is prepared by the coating process of the amorphous nanocrystalline magnetic powder as claimed in any one of claims 1 to 7; the method comprises the following steps:

[0026] The insulating coated magnetic powder is mixed with the binder solution, fully stirred and then dried, and the mixed magnetic powder is cold-pressed to obtain an amorphous magnetic powder core green body; the amorphous magnetic powder core green body is placed in an atmosphere protection furnace, kept at a second preset temperature for a preset time for stress relief heat treatment, and cooled with the furnace after the heat treatment is completed, so as to obtain an amorphous or nanocrystalline magnetic powder core.

[0027] Furthermore, the binder solution is an epoxy resin and acetone solution, and the amount of the binder solution is 2-5wt% of the weight of the insulation-coated magnetic powder.

[0028] Furthermore, the second preset temperature is 350-520° C., the preset time is 0.5-3 hours, and the pressure during cold pressing is 600-2000 MPa.

[0029] By adopting the technical solution of the present invention, at least the following beneficial effects are achieved:

[0030] 1. The plasma chemical vapor deposition method can be used to coat the amorphous magnetic powder below the crystallization temperature, and the problem of abnormal crystallization of the amorphous magnetic powder caused by excessively high temperature will not occur during the coating process. The plasma chemical vapor deposition process only takes a few minutes to complete, with good results in a short time, and can achieve short-time and efficient coating of the magnetic powder surface.

[0031] 2. By using the rotary chemical vapor deposition method, SiO2 film can be evenly deposited on the surface of the magnetic powder, so that the coated magnetic powder has better anti-rust performance and insulation properties.

[0032] 3. The prepared amorphous magnetic powder core or nanocrystalline magnetic powder core with SiO2 coating layer has higher magnetic permeability and lower loss, and has excellent anti-rust performance.

Brief Description of the Drawings

[0033] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0034] Figure 1 It is an overall flow chart of a coating process of amorphous nanocrystalline magnetic powder of the present invention;

[0035] Figure 2 This is a microscopic morphology characterization diagram of the magnetic powder prepared in Example 1 of the present invention. [Specific implementation method]

[0036] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0037] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0038] See also Figure 1 As shown, the present invention provides a coating process for amorphous nanocrystalline magnetic powder, wherein the entire process of the coating process includes magnetic powder coupling, drying, loading, vacuuming, passing N2O mixed gas, heating the deposition tube, rotating the deposition tube, microwave discharge, stopping discharge and vacuuming, passing N2O and SiH4 mixed gas, microwave discharge, stopping discharge and turning off heating, passing protective gas, cooling with the furnace, and completing coating; the coating process specifically includes the following steps:

[0039] Step 1, mixing magnetic powder and a coupling agent with an ethanol solution for coupling, and drying after mechanical stirring; wherein the magnetic powder can specifically be a spherical amorphous magnetic powder; the coupling agent (such as a silane coupling agent) is usually used together with the ethanol solution during the hydrolysis treatment to optimize its hydrolysis effect and reaction controllability;

[0040] Step 2, placing the coupled magnetic powder in a glass deposition tube for vapor deposition, and evacuating the glass deposition tube;

[0041] Step 3, introducing a mixed gas of Ar and N2O into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure, that is, closing the gas inlet valve of the glass deposition tube after the preset pressure is reached;

[0042] Step 4: using a heating device to heat the glass deposition tube to a first preset temperature, and starting the glass deposition tube to rotate at a preset rate, thereby driving the magnetic powder in the glass deposition tube to move, so that the magnetic powder is in a suspended state; wherein the heating device can specifically be a muffle furnace, and the glass deposition tube can be driven to rotate by a motor drive mechanism;

[0043] Step 5: Turn on the microwave generator to generate plasma and perform plasma pretreatment on the magnetic powder. In the specific implementation of the present invention, it is necessary to generate glow discharge in the glass deposition tube under the set power of the microwave generator, thereby generating Ar and N2O mixed plasma. The mixed plasma has a bombardment effect on the inner wall of the glass deposition tube under the action of microwaves, thereby playing the role of plasma cleaning and improving the inner surface structure; after the discharge reaches a preset discharge time, turn off the microwave generator, and evacuate the glass deposition tube again;

[0044] Step 6, introducing a mixed gas of Ar, N2O and SiH4 into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure, that is, closing the air inlet valve of the glass deposition tube after reaching the preset pressure, and keeping the glass deposition tube in a sealed state; since the reaction rate of SiH4 and N2O gases is very fast under microwave excitation, the uniformity of the film prepared by the conventional method of ventilation and deposition is very poor, and the film is mainly deposited at the air inlet; the present invention can well solve the problem of poor deposition uniformity through the sealed static gas method;

[0045] Step 7, turning on the microwave generator again to generate plasma, so that the mixed gas reacts and deposits a SiO2 film on the surface of the magnetic powder;

[0046] Step 8. After reaching the preset deposition time, turn off the heating equipment; introduce pure Ar gas into the glass deposition tube to discharge the reaction gas in the glass deposition tube, and after discharge, turn off the gas source and stop the rotation of the glass deposition tube; take out the magnetic powder after cooling it in the furnace to obtain the insulating coated magnetic powder.

[0047] In the present invention, in step 1, the magnetic powder is iron-based amorphous magnetic powder, and the composition of the iron-based amorphous magnetic powder is any one of FeSiB, FeSiBP, FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, FeSibBPCNbCu or a mixture of more. Of course, the above are only some specific embodiments of the present invention, but the present invention is not limited to this. Iron-based amorphous magnetic powders with other components can also be used in specific implementations.

[0048] In the present invention, the coupling agent is a silane coupling agent, and preferably, the silane coupling agent is one or a mixture of KH550, KH560, KH570, and KH792, and the amount of the coupling agent is 0.3-1wt% of the weight of the magnetic powder. The present invention introduces amino groups on the surface of the magnetic powder by using a coupling agent to perform surface coupling treatment on the magnetic powder, thereby enhancing the bonding force between the magnetic powder and the SiO2 coating layer. At the same time, the amount of the coupling agent should not exceed 1wt%, otherwise excessive addition will cause the final magnetic powder core to have more non-magnetic substances as a whole, thereby reducing the magnetic permeability.

[0049] In the present invention, in order to fully mix the magnetic powder and the coupling agent with the ethanol solution, the drying after mechanical stirring is specifically: drying after mechanical stirring for 30 minutes.

[0050] In the present invention, in step 2 and step 5, the vacuuming of the glass deposition tube is specifically: the vacuum degree of the glass deposition tube is drawn to less than 1×10 -2 Pa.

[0051] In the present invention, in step 3 and step 6, the preset pressure is 50-300Pa; the greater the pressure in the vacuum growth chamber, the shorter the chemical bonds of the gas molecules, the stronger the chemical bonds, the lower the deposition rate, and the phenomenon of insufficient reaction will occur, resulting in poor quality of the generated film; on the contrary, the lower the reaction pressure, the weaker the chemical bonds between the gas molecules, and the greater the deposition rate; but when the reaction pressure is too low, it will lead to a decrease in the number of gas molecules, a decrease in the density of ions participating in the reaction, and thus a decrease in the reaction rate. Therefore, the present invention controls the reaction pressure within 50-300Pa, which can ensure both the quality of the generated film and the deposition rate.

[0052] In step 6, the gas flow ratio of N2O to SiH4 is 2:1-4:1. By increasing the gas flow ratio of N2O to SiH4, the deposition rate can be increased and the density of the film can be improved; but once saturation is reached, the deposition rate will no longer change.

[0053] In the present invention, in step 4, the first preset temperature is 100-300°C; since the reaction temperature affects the atomic diffusion capacity, generally increasing the temperature will increase the deposition rate; when the temperature is low, the deposition rate is slow and the required reaction time is long, but when the temperature is too high, the deposition rate is too fast and will affect the density of the film. Therefore, the present invention controls the reaction temperature between 100-300°C, which can ensure the deposition rate without affecting the density of the film.

[0054] The preset rate is 10-30r / min; keeping the glass deposition tube rotating during the deposition process can drive the magnetic powder to rotate in the glass deposition tube and be in a suspended state, so that each particle of magnetic powder can be evenly coated; usually the rotation speed of the glass deposition tube will take the maximum value within the adjustable range of the equipment.

[0055] In the present invention, in step 5 and step 7, the power of the microwave generator is 10-100W; as the power of the microwave generator increases, the gas molecules dissipate more energy, and more ions and reactive substances are generated, thereby increasing the deposition rate of the film; however, too high a frequency will cause plasma instability, resulting in increased surface roughness of the film; therefore, in order to reduce the roughness of the film surface and ensure the deposition rate of the film, the present invention controls the power of the microwave generator between 10-100W.

[0056] And in step 5, in order to ensure the pretreatment effect, the preset discharge time is 1-10 minutes.

[0057] In the present invention, in step 8, the preset deposition time is 1-10 minutes to achieve a better deposition effect and achieve the characteristics of high rust prevention, high magnetic permeability and low loss. The deposition time corresponds to the thickness of the SiO2 layer. The longer the deposition time, the thicker the film thickness on the surface of the magnetic powder. In the specific implementation of the present invention, the thickness of different SiO2 coating layers can be adjusted by adjusting the deposition time, that is, adjusting the content of non-magnetic substances in the magnetic powder core.

[0058] The present invention provides a method for preparing a magnetic powder core, wherein the method requires the use of insulating coated magnetic powder, wherein the insulating coated magnetic powder is prepared by a coating process of amorphous nanocrystalline magnetic powder, and the coating process of amorphous nanocrystalline magnetic powder is specifically described in detail above, which will not be described in detail here; the method comprises the following steps:

[0059] The insulating coated magnetic powder is mixed with the binder solution, fully stirred and then dried, and the mixed magnetic powder is cold-pressed to obtain an amorphous magnetic powder core green body; the amorphous magnetic powder core green body is placed in an atmosphere protection furnace, kept at a second preset temperature for a preset time for stress relief heat treatment, and cooled with the furnace after the heat treatment is completed, so as to obtain an amorphous or nanocrystalline magnetic powder core.

[0060] In the present invention, the binder solution is an epoxy resin and acetone solution. In a specific implementation, the acetone solution can be added to the epoxy resin as a solvent or diluent for the epoxy resin, which helps to reduce the viscosity of the epoxy resin and makes it easier to handle. The amount of the epoxy resin used is 2-5wt% of the weight of the insulating coated magnetic powder, which ensures that the performance of the prepared magnetic powder core (such as reduced magnetic permeability) will not be affected by excessive binder, and ensures that the magnetic powders can be reliably bonded together.

[0061] In the present invention, in order to ensure the forming effect, the pressure during cold pressing is 600-2000MPa.

[0062] The second preset temperature is 350-520° C., and the preset time is 0.5-3 hours. In the specific implementation of the present invention, the second preset temperature and the preset time can be set according to different processing requirements of amorphous or nanocrystalline magnetic powder cores.

[0063] By adopting the above technical solution of the present invention, at least the following beneficial effects are achieved:

[0064] 1. The plasma chemical vapor deposition method can be used to coat the amorphous magnetic powder below the crystallization temperature, and the problem of abnormal crystallization of the amorphous magnetic powder caused by excessively high temperature will not occur during the coating process. The plasma chemical vapor deposition process only takes a few minutes to complete, with good results in a short time, and can achieve short-time and efficient coating of the magnetic powder surface.

[0065] 2. By using the rotary chemical vapor deposition method, SiO2 film can be evenly deposited on the surface of the magnetic powder, so that the coated magnetic powder has better anti-rust performance and insulation properties.

[0066] 3. The prepared amorphous magnetic powder core or nanocrystalline magnetic powder core with SiO2 coating layer has higher magnetic permeability and lower loss, and has excellent anti-rust performance.

[0067] The technical solution of the present invention is further described in detail below through some specific embodiments and comparative examples:

[0068] Example 1

[0069] The spherical FeSiBNbCu magnetic powder was mixed with a silane coupling agent / ethanol solution (i.e., a silane coupling agent and an ethanol solution), wherein the amount of the silane coupling agent was 0.5wt% of the weight of the magnetic powder. After mechanical stirring for 30 minutes, the magnetic powder surface was coupled and dried. The coupled magnetic powder was then placed in a glass deposition tube for vapor deposition and evacuated to 5×10 -3Pa. A mixed gas of Ar and N2O was introduced into the glass deposition tube until the pressure reached 100Pa, and then the inlet valve was closed. The muffle furnace was turned on to heat the glass deposition tube to 300°C, and the motor mechanism was started to drive the glass deposition tube containing magnetic powder to rotate at a speed of 25r / min. After the glass deposition tube rotated stably, the microwave generator was turned on to generate plasma, and the RF power was adjusted to 100W. After the magnetic powder was pretreated with plasma for 1 minute, the microwave generator was turned off and the vacuum was evacuated to 5×10 -3 Pa. Then, a mixed gas of Ar, N2O and SiH4 is introduced into the glass deposition tube, where the gas flow ratio of N2O and SiH4 is 3:1. When the pressure in the glass deposition tube reaches 100Pa, the air inlet valve is closed to keep the glass deposition tube in a closed state. The microwave generator is turned on again, and the RF power is adjusted to 100W to generate plasma, so that the mixed gas reacts to obtain a SiO2 film and deposits on the surface of the magnetic powder; the deposition ends after 4 minutes, the muffle furnace is closed, and pure Ar gas is introduced into the glass deposition tube to discharge the reaction gas in the glass deposition tube. After the gas is discharged, the gas source is turned off and the rotation of the glass deposition tube is stopped, and the magnetic powder is taken out after cooling with the furnace.

[0070] Then, the SiO2 coated amorphous soft magnetic powder is mixed with epoxy resin and acetone solution, the amount of epoxy resin used is 2wt% of the weight of the insulating coated magnetic powder, and then dried after being fully stirred. The amorphous magnetic powder core green body is pressed and formed in a mold under a pressure of 1600MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 500℃ for 1 hour for stress relief heat treatment. After the heat treatment is completed, it is cooled with the furnace to obtain an amorphous or nanocrystalline magnetic powder core.

[0071] Example 2

[0072] The spherical FeSiBNbCu magnetic powder was mixed with a silane coupling agent / ethanol solution (i.e., a silane coupling agent and an ethanol solution), wherein the amount of the silane coupling agent was 0.5wt% of the weight of the magnetic powder. After mechanical stirring for 30 minutes, the magnetic powder surface was coupled and dried. The coupled magnetic powder was then placed in a glass deposition tube for vapor deposition and evacuated to 5×10 -3 Pa. A mixed gas of Ar and N2O was introduced into the glass deposition tube until the pressure reached 100Pa, and then the inlet valve was closed. The muffle furnace was turned on to heat the glass deposition tube to 300°C, and the motor mechanism was started to drive the glass deposition tube containing magnetic powder to rotate at a speed of 25r / min. After the glass deposition tube rotated stably, the microwave generator was turned on to generate plasma, and the RF power was adjusted to 50W. After the magnetic powder was pretreated with plasma for 2 minutes, the microwave generator was turned off and the vacuum was evacuated to 5×10 -3Pa. Then, a mixed gas of Ar, N2O and SiH4 is introduced into the glass deposition tube, where the gas flow ratio of N2O and SiH4 is 3:1. When the pressure in the glass deposition tube reaches 100Pa, the air inlet valve is closed to keep the glass deposition tube in a closed state. The microwave generator is turned on again, and the RF power is adjusted to 50W to generate plasma, so that the mixed gas reacts to obtain a SiO2 film and deposits on the surface of the magnetic powder; the deposition ends after 8 minutes, the muffle furnace is closed, and pure Ar gas is introduced into the glass deposition tube to discharge the reaction gas in the glass deposition tube. After the gas is discharged, the gas source is turned off and the rotation of the glass deposition tube is stopped, and the magnetic powder is taken out after cooling with the furnace.

[0073] Then, the SiO2 coated amorphous soft magnetic powder is mixed with epoxy resin and acetone solution, the amount of epoxy resin used is 2wt% of the weight of the insulating coated magnetic powder, and then dried after being fully stirred. The amorphous magnetic powder core green body is pressed and formed in a mold under a pressure of 1600MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 500℃ for 1 hour for stress relief heat treatment. After the heat treatment is completed, it is cooled with the furnace to obtain an amorphous or nanocrystalline magnetic powder core.

[0074] Example 3

[0075] The spherical FeSiBNbCu magnetic powder was mixed with a silane coupling agent / ethanol solution (i.e., a silane coupling agent and an ethanol solution), wherein the amount of the silane coupling agent was 0.3wt% of the weight of the magnetic powder. After mechanical stirring for 30 minutes, the magnetic powder surface was coupled and dried. The coupled magnetic powder was then placed in a glass deposition tube for vapor deposition and evacuated to 5×10 -3 Pa. A mixed gas of Ar and N2O was introduced into the glass deposition tube until the pressure reached 30Pa, and the inlet valve was closed. The muffle furnace was turned on to heat the glass deposition tube to 100°C, and the motor mechanism was started to drive the glass deposition tube containing magnetic powder to rotate at a speed of 25r / min. After the glass deposition tube rotated stably, the microwave generator was turned on to generate plasma, and the RF power was adjusted to 10W. After the magnetic powder was pretreated with plasma for 1 minute, the microwave generator was turned off and the vacuum was evacuated to 5×10 -3 Pa. Then, a mixed gas of Ar, N2O and SiH4 is introduced into the glass deposition tube, where the gas flow ratio of N2O and SiH4 is 4:1. When the pressure in the glass deposition tube reaches 30Pa, the air inlet valve is closed to keep the glass deposition tube in a closed state. The microwave generator is turned on again, and the RF power is adjusted to 10W to generate plasma, so that the mixed gas reacts to obtain a SiO2 film and deposits on the surface of the magnetic powder; the deposition ends after 10 minutes, the muffle furnace is closed, and pure Ar gas is introduced into the glass deposition tube to discharge the reaction gas in the glass deposition tube. After the gas is discharged, the gas source is turned off and the rotation of the glass deposition tube is stopped, and the magnetic powder is taken out after cooling with the furnace.

[0076] Then, the SiO2 coated amorphous soft magnetic powder is mixed with epoxy resin and acetone solution, the amount of epoxy resin used is 2wt% of the weight of the insulating coated magnetic powder, and then dried after being fully stirred. The amorphous magnetic powder core green body is pressed and formed in a mold under a pressure of 600MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 500℃ for 0.5 hours for stress relief heat treatment. After the heat treatment is completed, it is cooled with the furnace to obtain an amorphous or nanocrystalline magnetic powder core.

[0077] Example 4

[0078] The spherical FeSiBNbCu magnetic powder was mixed with a silane coupling agent / ethanol solution (i.e., a silane coupling agent and an ethanol solution), wherein the amount of the silane coupling agent was 1 wt% of the weight of the magnetic powder. After mechanical stirring for 30 minutes, the magnetic powder surface was coupled and dried. The coupled magnetic powder was then placed in a glass deposition tube for vapor deposition and evacuated to 5×10 -3 Pa. A mixed gas of Ar and N2O was introduced into the glass deposition tube until the pressure reached 300Pa, and then the inlet valve was closed. The muffle furnace was turned on to heat the glass deposition tube to 300°C, and the motor mechanism was started to drive the glass deposition tube containing magnetic powder to rotate at a speed of 25r / min. After the glass deposition tube rotated stably, the microwave generator was turned on to generate plasma, and the RF power was adjusted to 100W. After the magnetic powder was pretreated with plasma for 10 minutes, the microwave generator was turned off and the vacuum was evacuated to 5×10 -3 Pa. Then, a mixed gas of Ar, N2O and SiH4 is introduced into the glass deposition tube, where the gas flow ratio of N2O and SiH4 is 2:1. When the pressure in the glass deposition tube reaches 300Pa, the air inlet valve is closed to keep the glass deposition tube in a closed state. The microwave generator is turned on again, and the RF power is adjusted to 100W to generate plasma, so that the mixed gas reacts to obtain a SiO2 film and deposits on the surface of the magnetic powder; the deposition ends after 10 minutes, the muffle furnace is closed, and pure Ar gas is introduced into the glass deposition tube to discharge the reaction gas in the glass deposition tube. After the gas is discharged, the gas source is turned off and the rotation of the glass deposition tube is stopped, and the magnetic powder is taken out after cooling with the furnace.

[0079] Then, the SiO2 coated amorphous soft magnetic powder is mixed with epoxy resin and acetone solution, the amount of epoxy resin used is 2wt% of the weight of the insulating coated magnetic powder, and then dried after being fully stirred. The amorphous magnetic powder core green body is pressed and formed in a mold under a pressure of 2000MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 520℃ for 3 hours for stress relief heat treatment. After the heat treatment, it is cooled with the furnace to obtain an amorphous or nanocrystalline magnetic powder core.

[0080] Comparative Example 1

[0081] The comparative example 1 and the example 1 both use spherical FeSiBNbCu magnetic powders, and the difference from the example 1 is that the comparative example 1 does not coat the amorphous magnetic powders, but directly mixes the amorphous magnetic powders with epoxy resin and acetone solution, the amount of epoxy resin used is 2wt% of the weight of the insulating coated magnetic powders, and then fully stirs and dries. The amorphous magnetic powder core green body is pressed and molded in a mold under a pressure of 1600MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 500℃ for 1 hour for stress relief heat treatment, and then cooled with the furnace after the heat treatment, thereby obtaining an amorphous or nanocrystalline magnetic powder core.

[0082] Comparative Example 2

[0083] The spherical FeSiBNbCu magnetic powders used in Comparative Example 2 and Example 1 are different from Example 1 in that: Comparative Example 2 does not use the coating process of the present invention to coat the amorphous magnetic powder, but mixes the amorphous magnetic powder with phosphoric acid and ethanol solution for treatment, the amount of phosphoric acid and ethanol solution is 0.5wt% of the weight of the amorphous magnetic powder, and then adds epoxy resin and acetone solution to mix after sufficient stirring, the amount of epoxy resin is 2wt% of the weight of the insulating coated magnetic powder, and then dry after sufficient stirring. The amorphous magnetic powder core green body is pressed and molded in a mold under a pressure of 1600MPa, and then the amorphous magnetic powder core green body is placed in an atmosphere protection furnace and kept at 500℃ for 1 hour for stress relief heat treatment, and cooled with the furnace after the heat treatment, thereby obtaining an amorphous or nanocrystalline magnetic powder core.

[0084] Comparative Example 3

[0085] The difference between Comparative Example 3 and Example 4 is that: in the deposition process of Comparative Example 3, the RF power is adjusted to 150 W, and the deposition is completed after 30 minutes; the other contents are exactly the same as Example 4.

[0086] Testing: The microscopic morphology of the magnetic powder prepared in the above-mentioned Example 1 was characterized, and the magnetic properties of the magnetic powder cores prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-3 were measured.

[0087] FIB-SEM was used to characterize the microstructure of the magnetic powder cross section and the thickness of the coating layer; a broadband LCR tester was used to measure the effective magnetic permeability μ of the sample at 100 kHz. e And the magnetic permeability under bias magnetic field; at the same time, the power analyzer was used to measure the sample at f = 100kHz, B m =Total loss at 100mT. Figure 2 The microscopic morphology of the magnetic powder obtained in Example 1 is shown in FIG. Figure 2It can be seen that a dense SiO2 coating layer has been wrapped around the magnetic powder, and its thickness is about 120nm.

[0088] The specific test results of the magnetic powder core are shown in the following table:

[0089]

[0090] It can be seen from the above comparison that the technical solution of the present invention can deposit a dense SiO2 coating layer on the surface of the magnetic powder, thereby improving the insulation and ensuring the rust-proof performance. At the same time, compared with the traditional method of not coating or using phosphoric acid and ethanol solution treatment, the density and DC bias characteristics of the magnetic powder core can be effectively improved, and the loss can be further reduced. In addition, it can be seen from Comparative Example 3 that when the RF power of the microwave generator is too high and the deposition time is too long, the phenomenon of "over-coating" will occur, which is manifested as a lot of flocs between the powders, and there are fine powders that are coated by a whole piece of larger silicon oxide to form large agglomerates, which leads to an increase in the surface roughness of the film, and at the same time greatly reduces the magnetic permeability and increases the hysteresis loss.

[0091] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. A coating process for amorphous nanocrystalline magnetic powder, characterized in that: The coating process comprises the following steps: Step 1, mixing magnetic powder and coupling agent with ethanol solution for coupling, and drying after mechanical stirring; Step 2, placing the coupled magnetic powder in a glass deposition tube for vapor deposition, and evacuating the glass deposition tube; Step 3, introducing a mixed gas of Ar and N2O into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure; Step 4: using a heating device to heat the glass deposition tube to a first preset temperature, and starting the glass deposition tube to rotate at a preset speed, thereby driving the magnetic powder in the glass deposition tube to move; Step 5, turning on the microwave generator to generate plasma and performing plasma pretreatment on the magnetic powder; after the discharge reaches a preset discharge time, turning off the microwave generator and evacuating the glass deposition tube again; Step 6, introducing a mixed gas of Ar, N2O and SiH4 into the glass deposition tube, and closing the gas source after the pressure in the glass deposition tube reaches a preset pressure, and keeping the glass deposition tube in a sealed state; Step 7, turning on the microwave generator again to generate plasma, so that the mixed gas reacts and deposits a SiO2 film on the surface of the magnetic powder; Step 8. After reaching the preset deposition time, turn off the heating equipment; introduce pure Ar gas into the glass deposition tube to discharge the reaction gas in the glass deposition tube, and after discharge, turn off the gas source and stop the rotation of the glass deposition tube; take out the magnetic powder after cooling it in the furnace to obtain the insulating coated magnetic powder.

2. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In the step 1, the magnetic powder is iron-based amorphous magnetic powder, and the composition of the iron-based amorphous magnetic powder is any one of FeSiB, FeSiBP, FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, and FeSibBPCNbCu, or a mixture of multiple thereof; The coupling agent is a silane coupling agent, and the silane coupling agent is one or a mixture of KH550, KH560, KH570, and KH792, and the amount of the coupling agent is 0.3-1wt% of the weight of the magnetic powder; The drying after mechanical stirring specifically includes: drying after mechanical stirring for 30 minutes.

3. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In step 2 and step 5, the vacuuming of the glass deposition tube is specifically: the vacuum degree of the glass deposition tube is drawn to less than 1×10 - 2 Pa.

4. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In step 3 and step 6, the preset pressure is 50-300 Pa; and in step 6, the gas flow ratio of N2O and SiH4 is 2:1-4:

1.

5. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In step 4, the first preset temperature is 100-300° C., and the preset speed is 10-30 r / min.

6. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In step 5 and step 7, the power of the microwave generator is 10-100 W; and in step 5, the preset discharge time is 1-10 minutes.

7. The coating process of amorphous nanocrystalline magnetic powder according to claim 1, characterized in that: In the step 8, the preset deposition time is 1-10 minutes.

8. A method for preparing a magnetic powder core, characterized in that: The preparation method requires the use of insulating coated magnetic powder, which is prepared by the coating process of the amorphous nanocrystalline magnetic powder according to any one of claims 1 to 7; the preparation method comprises the following steps: The insulating coated magnetic powder is mixed with the binder solution, fully stirred and then dried, and the mixed magnetic powder is cold-pressed to obtain an amorphous magnetic powder core green body; the amorphous magnetic powder core green body is placed in an atmosphere protection furnace, kept at a second preset temperature for a preset time for stress relief heat treatment, and cooled with the furnace after the heat treatment is completed, so as to obtain an amorphous or nanocrystalline magnetic powder core.

9. A method for preparing a magnetic powder core according to claim 8, characterized in that: The binder solution is an epoxy resin and acetone solution, and the amount of the epoxy resin used is 2-5wt% of the weight of the insulating coated magnetic powder.

10. The method for preparing a magnetic powder core according to claim 8, characterized in that: The second preset temperature is 350-520° C., the preset time is 0.5-3 hours, and the pressure during cold pressing is 600-2000 MPa.

Citation Information

Patent Citations

  • A CVD-coated iron-silicon alloy powder and an iron-silicon magnetic powder core and their preparation method

    CN112466589B

  • Preparation method of iron-based amorphous magnetic powder core

    CN116435085A